Investigation and experimental work on power generation by piezoelectric devices - Muhammad Faiz Nor, Mohd Fozi (2012)
This project was carried out to study the characteristics of different types of piezoelectric device and experimental work on how to obtain power generation by piezoelectric device. The objectives of this research are to investigate the different characteristic from different types of piezoelectric device and to find the method how to obtain power generation by piezoelectric devices. A test rig consists of the releaser, steel ball, specimen holder, and ruler to run this experiment. The types of piezoelectric used are single layer piezoelectric disc and two layer piezoelectric discs. The voltage produces from the piezoelectric devices are from the different impact forces applied on the device. The impact forces are from the steel ball which is release from different heights. The voltage signal produced from piezoelectric was captured by electrical device called oscilloscope. The voltage output for the single layer piezoelectric and two layers piezoelectric at the different impact force were recorded and analyzed. All the value recorded was compared to the different impact force applied. The result shows that the voltage output from the single layer piezoelectric are higher than the voltage output from the two layers piezoelectric at any impact force applied. The deflection of the piezoelectric is directly proportional to the voltage output. The conclusion has shown that the voltage produces by two layers piezoelectric are lower than single layer piezoelectric because the placement of the specimen is not optimum which mean there is limitation for the specimen to gain maximum deflection.